Effect of pore-size distribution on saturated shear strength of residual soil - Eng, Aik How (2009)
Residual soils are formed from weathered rocks and are usually under unsaturated conditions. Pore-size distribution controls the engineering properties of the soil and it is an important aspect in Geotechnical Engineering. Laboratory experiments to investigate how pore-size distribution (PSD) affects saturated shear strength of residual soils were conducted. Tempe cell, triaxial, pressure plate and salt solution tests are carried out to obtain the soil-water characteristic curve (SWCC) of granitic Bukit Timah formation in Singapore. Index property and consolidated undrained triaxial tests on saturated samples are also performed.